The Role of Artificial Intelligence (AI) in Islamic Religious Education Learning: Solution or Challenge? - Meriyati, Meriyati; Sampurna, Azet; Pratama, Angga; Bagaskara, Figo Rangga; Rahmah, Fadila; Jatmiko, Agus; Amriyah, Chairul (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
The rapid development of technology continues to influence education. Advanced technology can be a solution or even a challenge in education.This study aims to understood and describe the solutions and challenges of using Artificial Intelligence (AI) in Islamic Religious Education Learning. The results of the study indicate that the use of AI in Islamic religious education learning has great potential in Islamic religious education learning. However, there are also challenges related to the use of AI in learning activities. In the long term, AI can be a very valuable tool to support Islamic religious education learning, as long as it is used wisely and well integrated into the learning system. Personalized learning, automated assessments, virtual tutoring, intelligent content, and presentation translation are some examples of the benefits of AI for education. AI can be a solution, but by paying attention to the challenges of using AI in Islamic Religious Education learning.